The weaponization of global payment infrastructures: A strategic dilemma - Andreas Nölke (Leibniz Institute for Financial Research SAFE, 2022)
The sixth sanction package of the European Union in the context of the aggression against Ukraine excludes Sberbank, the largest Russian bank, from the SWIFT network. The increasing use of SWIFT as a tool for sanctions stimulates the rollout of alternative payment information systems by the governments of Russia and China. This policy white paper informs about the alternatives at hand, as well as their advantages and disadvantages. Careful reflection about these issues is particularly important, given the call for an "Economic Article 5" tabled for the next NATO meeting. Finally, the white paper highlights the need for institutional reforms, if policymakers decide to return SWIFT to the status of a global public good after the war.
Keywords: 330; Ukraine; Russia; Sanctions; SWIFT